EARTHWORM DIVERSITY AND ABUNDANCE IN SELECTED DUMPSITES IN IBADAN, AND TOXICITY OF CONTAMINATED WATER ON ASSOCIATED FAUNA (2016)
Huge quantities of wastes which are indiscriminately disposed into uncontrolled dumpsites and flowing waters around residential areas are generated from Ibadan, metropolis. These may adversely affect soil, surface- and ground-water qualities and the fauna. Limited information exists on toxic effects that wastes from these non-designated sites have on associated fauna. Earthworms are one of the dominant fauna in soils and are pollution bioindicators. Therefore this study was designed to investigate physico-chemical parameters, earthworm diversity and abundance, and acute toxicity of contaminated-water on some fauna in selected dumpsites in Ibadan. One-hundred and twenty water samples from streams (Irefin, Gege, Gbagi, Odinjo, and Omi-Adio) receiving domestic wastes; 60-composite soil samples each from dumpsites (Ojokondo, Olodo, Moniya, Idi-Ope and Oremeji) and stream banks; 12-composite soil samples from a control site at University of Ibadan (UI); 72 groundwater samples from wells around the dumpsites and UI were purposively collected once every two months from March 2008 to February 2010. Earthworms from top-soil were sampled using 0.25x0.25 m2 quadrat, handpicked, identified and density determined following standard procedures. Earthworm species’ diversity and evenness were determined using Shannon-Wiener diversity index and Shannon’s evenness, respectively. Water samples were analysed for physico-chemical parameters [including Dissolved-Oxygen (DO), Biochemical-Oxygen-Demand (BOD), and Chemical-Oxygen-Demand (COD)] and soil samples including lead and zinc using standard methods and results were compared with NESREA standards. The 48-hour-LC50 of stream-samples were determined for Cloeon perkinsi (mayfly) larvae (CP); while 96-hour-LC50 for Rana temporaria tadpoles, Clarias gariepinus frys (CG1) and fingerlings (CG2) were determined using Probit method. Data were analysed using descriptive statistics and ANOVA at p=0.05. Three earthworm species (Eudrilus euginiae, Dichogaster modigliani and Hyperiodrilus africanus) were identified at UI, streams and dumpsites. Highest density of Eudrilus euginiae (30.0±13.7/m2) was recorded at UI and this was significantly different from other sites, while lowest (6.4±2.2/m2) was recorded at Ojokondo. Highest densities of Hyperiodrilus africanus (32.7±14.6/m2) and Dichogaster modigliani (40.0±0.0/m2) were recorded at UI and Gbagi, respectively; while lowest value of 4.0±0.0/m2 was recorded at Irefin and Gege. Eudrilus euginiae and Dichogaster modigliani were not found at Gege and Idi-Ope, respectively, while Hyperiodrilus africanus was not found at Odinjo, Moniya and Olodo. Earthworm diversity (0.5) was highest in UI and lowest (0.3) at Gege. Earthworms were most evenly distributed at Odinjo (2.4) and least at Ojokondo (0.8). The DO (mg/L) for streams ranged from (0.4±0.4) to (2.6±0.6) and were lower than permissible limit for aquatic life. Lead (260.6±77.7mg/kg, 269.6±46.4mg/kg) and zinc (456.9±69.9mg/kg, 1685.1±420.3mg/kg) values in Gege and Ojokondo soils, respectively were significantly higher than NESREA limits. In all groundwater samples, BOD (46.7±21.0mg/L) and COD (154.0±7.0mg/L) exceeded NESREA limits. The 48-hour-LC50 of stream-water to CP (Irefin, 12.7%; Gege, 8.6%), and 96-hour-LC50 to CGI (Gege, 0.8%; Gbagi, 2.8%) and CG2 (Gege, 3.3%; Irefin, 0.6%) indicated high toxicity of the sites. The low earthworm abundance, poor physico-chemical qualities and high toxicity of the study sites revealed that the soil, streams and groundwater were polluted in Ibadan. Consequently, there is need for adequate management and disposal of solid-wastes to prevent further environmental contamination.